Penerapan TOGAF ADM untuk Pemodelan Blueprint Arsitektur Enterprise pada SMK Berinfrastruktur TI Minim - Mulyana, Wide; Noviana, Noviana; Putri, Zelviannisa; Asniwati, Asniwati; Wahyuna, Nurul (JURNAL FASILKOM, 2026)
The integration of information and communication technology (ICT) in education is increasingly important, yet many vocational secondary schools (SMK) in Indonesia still lack adequate IT infrastructure and enterprise architecture planning. SMK Sulthan Muazzam Syah Pekanbaru, accredited “C” by the National Accreditation Board (BAN), is one such institution that operates without a systematic IT blueprint to guide technological development. This research aims to design an enterprise architecture-based IT blueprint for the school using The Open Group Architecture Framework Architecture Development Method (TOGAF ADM), covering six phases selected from the full TOGAF ADM cycle: Preliminary, Architecture Vision, Business Architecture, Information Systems Architecture, Technology Architecture, and Opportunities & Solutions. Data were collected through structured interviews with five key stakeholders and direct observation. The results produced four main architectural artifacts: an enterprise architecture blueprint encompassing business, data, application, and technology domains; three entity-relationship diagrams for the online admissions, e-learning, and academic information systems; phased technology infrastructure recommendations, including hardware and network topology upgrades; and a seven-stage, three-month system implementation roadmap. This study contributes an operational enterprise architecture model for resource-constrained vocational schools in Indonesia, addressing a gap in prior TOGAF ADM research that has largely focused on universities and private organizations. The proposed blueprint has the potential to serve as a reference governance framework for similar institutions undergoing ICT transformation, although its transferability to other contexts still needs to be tested empirically.